Effect of Brace Configuration on Two-Dimensional (2D) Frame Structure (Zona Laut Jurnal Inovasi Sains Dan Teknologi Kelautan, 2020)
The portal structure generally consists of 2 and 3 dimensions, the loads that work on it are also varied adapted to the purpose of the portal itself is used. A portal structure of either 2 or 3 dimensions is a tructure composed of beams and columns, so it is generally reinforced with a diagonal stem called a brace. The study aims to analyse the influence ofbrace configurations on 2-dimensional portals. The structure is modeled after a varied configuration of brace consisting of 5 models. The condition of the fifth boundary of the model is the joints and clamp with a constant axial load point working on the vertical pole. The portal dimensions, yield voltage, modulus of elasticity and poison ratio are assumed to be constant. For modeling, computation and analysis, used computer auxiliary programs namely SAP 2000. The results gained are focus reactions, point displacement and deformation of the five models.
Keywords: Portal 2D, Configuration of Brace, SAP 2000.